FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMILIH PRODUK YAMAHA LEXI DI DEALER ISTANA MOTOR KLUNGKUNG-BALI - I Kadek Rizki Pramana Putra; Ni Made Hartini (Universitas Triatma Mulya, 2022)
This study aims to analyze the factors that determine consumer decisions in choosing Yamaha Lexi products at the Istana Motor Dealer Klungkung-Bali. Sampling was done by using purposive sampling technique, where the number of samples used in this study was 85 respondents. In this study, statistical analysis was carried out with the help of the computer program SPSS (Statistical for Social Science) 24 for windows. The results of this study indicate that; the marketing factor has the highest eigenvalue, which is 2.819 and is able to explain the total variance of 16.585%. The superiority factor has a fairly high eigenvalue of 2.536% and is able to explain the total variance of 14,917. The supporting factor has an eigenvalue of 1.909 and is able to explain the total variance of 11.232. The Technology factor has an eigenvalue of 1,485 and is able to explain the total variance of 8,734. The supporting factor has an eigenvalue of 1,308 and is able to explain the total variance of 7,695 and the Service Factor has an eigenvalue of 1,141 and is able to explain the total variance of 6,714.